Business Model Canvas: Online Business Strategy at Pekanbaru Fishing Equipment Store - Muhammad Fahrozi; Nia Anggraini; Irsyadi Zain; Erfa Okta Lussianda; Awliya Afwa (MultiTech Publisher, 2024)
This research explores the feasibility of an online business strategy for